THE MORPHOLOGY OF PATHOGENIC FUNGI AS THE CAUSE OF ROTTEN CACAO (THEOBROMA CACAO L.) FRUITS IN TUMBA VILLAGE - Yuliana Nurdian Toini; Novri Youla Kandowangko; Wirnangsi D Uno (Fakultas MIPA Universitas Negeri Gorontalo, 2021)
The purpose of this qualitative descriptive study was to find out the types of pathogenic fungi that caused rotten cacao fruits based on morphological characteristics in Tumba village. Fungi isolation was performed by employing the moist chamber method with the PDA medium. Moreover, the identification of pathogenic fungal isolates followed the morphological characteristics mentioned earlier. The results showed that four fungal isolates contributed to the rotting of cacao fruits in the site area. Fungal isolate Tumba 1 (T1) had morphological characteristics of a white colony with smooth surface, and oval sporangium with a bulge on its tip; fungal isolate Tumba 2 (T2) consisted of morphological characteristics of a white colony with a pink circle in the middle, and having a sickle-shaped and oval macroconidia; fungal isolate Tumba 3 (T3) comprised morphological characteristics of a dark black colony with irregular shape, uneven edge, and having a long conidiophore with a big conidial head; fungal isolate Tumba 4 (T4) had morphological characteristics of a black colony with a white circle in the middle, uneven edge, and having a tube-shaped conidium. As based on the morphological characteristics, it was assumed that the four fungal isolates causing the rotten cacao fruit were similar to the types of fungi, i.e., Phytopthora palmivora, Fusarium sp, Aspergilus niger, and Gloeosprorium sp.